2021
DOI: 10.3390/ijms22062837
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulatory Networks Associate with Early Stages of Potato Virus X Infection of Solanum tuberosum

Abstract: Potato virus X (PVX) belongs to genus Potexvirus. This study characterizes the cellular transcriptome responses to PVX infection in Russet potato at 2 and 3 days post infection (dpi). Among the 1242 differentially expressed genes (DEGs), 268 genes were upregulated, and 37 genes were downregulated at 2 dpi while 677 genes were upregulated, and 265 genes were downregulated at 3 dpi. DEGs related to signal transduction, stress response, and redox processes. Key stress related transcription factors were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 107 publications
(166 reference statements)
0
2
0
Order By: Relevance
“…Because no accessions occurs under the rice tab, a note appears saying “External Identifiers‐NOT AVAILABLE for selected plant species.” Upon selecting the potato tab and then the Spud DB locus accession, the hotlink directs you to the Spud DB Potato Genomics Resource page for the locus. This gene in the SPUD DB is identified as a bZIP transcription factor family protein, however, Herath and Verchot (2021) identified this gene as StbZIP17 ; the putative ortholog of Arabidopsis bZIP17 . This locus is also identified in NCBI as StbZIP17 .…”
Section: Resultsmentioning
confidence: 99%
“…Because no accessions occurs under the rice tab, a note appears saying “External Identifiers‐NOT AVAILABLE for selected plant species.” Upon selecting the potato tab and then the Spud DB locus accession, the hotlink directs you to the Spud DB Potato Genomics Resource page for the locus. This gene in the SPUD DB is identified as a bZIP transcription factor family protein, however, Herath and Verchot (2021) identified this gene as StbZIP17 ; the putative ortholog of Arabidopsis bZIP17 . This locus is also identified in NCBI as StbZIP17 .…”
Section: Resultsmentioning
confidence: 99%
“…In plants, transcription factors of the WRKY, AP2/ERF, bZIP, bHLH, MYB, and NAC families are important in gene regulatory networks against various biotic and abiotic stresses in different plants ( Shen et al, 2012 ; Wang et al, 2018; Li et al, 2020 ; Yan et al, 2020 ; Gao et al, 2021 ; Herath & Verchot, 2021 ). Our study found that 9 WRKYs, 7 AP2/ERFs, 5 bHLHs, 4 bZIPs, 4 MYBs, and 4 NACs were closely correlated with genes involved in the phenylpropanoid synthesis and the lignin synthesis.…”
Section: Discussionmentioning
confidence: 99%